2021
DOI: 10.3390/nano11123176
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Sol–Gel Preparation of the Nanostructured Magnetic System for Solid-Phase Synthesis

Abstract: This work describes a new synthesis method for core–shell magnetite nanoparticles with a secondary silica shell, functionalized with a linker system (Fe3O4-PABA-SiO2-linker) using a microwave-assisted heating technique. The functionalized solid nanomaterial was used for the nanophase synthesis of peptides (Fmoc route) as a solid support. The co-precipitation method was selected to obtain magnetite nanoparticles and sol–gel technique for silica coating using a microwave-assisted (MW) procedure. The magnetic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…The surface functionalization was an important target, as it prevents the agglomeration of the nanoparticles, thus allowing a homogeneous particle dispersion within our final system, the magnetic film. Fe 3 O 4 and Fe 3 O 4 /malic samples revealed a mutual peak corresponding to Fe–O stretching vibration, at ~550 cm −1 , normally reported in previous studies [ 38 , 39 ]. The large absorption bands centered around 3345 cm −1 , present in both samples, are assigned to –OH stretching vibrations, while Fe 3 O 4 additionally presents a very faint absorption band at 1630 cm −1 , attributed to –OH bending vibrations.…”
Section: Resultssupporting
confidence: 82%
“…The surface functionalization was an important target, as it prevents the agglomeration of the nanoparticles, thus allowing a homogeneous particle dispersion within our final system, the magnetic film. Fe 3 O 4 and Fe 3 O 4 /malic samples revealed a mutual peak corresponding to Fe–O stretching vibration, at ~550 cm −1 , normally reported in previous studies [ 38 , 39 ]. The large absorption bands centered around 3345 cm −1 , present in both samples, are assigned to –OH stretching vibrations, while Fe 3 O 4 additionally presents a very faint absorption band at 1630 cm −1 , attributed to –OH bending vibrations.…”
Section: Resultssupporting
confidence: 82%
“…Microwave-assisted synthesis has emerged as a powerful tool for material synthesis (Zengin et al, 2023) (Santos et al, 2021) due to its rapid processing, lower energy consumption, and enhanced control over material properties (Istrati et al, 2021) (Bucek et al, 2019). However, limited research has been conducted on tailoring the properties of silica gel, specifically the silanol group content, through microwave synthesis for improved moisture adsorption (Zhuravlev & Potapov, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For example, they demonstrated that although Fe 3 O 4 -P resulted in the CO 2 absorption capacity of pure water and NMP solution increasing roughly to 25.07 and 15.88%, its performance was truly negligible when it was used in sulfinol. ,, Likewise, Arshadi et al used Fe 3 O 4 @SiO 2 -NH 2 nanodispersion at a high concentration of 0.4 wt %, which promoted CO 2 uptake up to 70% and with respect to pure water as a base solvent in a bubble column system as a semicontinuous mode . The reason for the high stability of Fe 3 O 4 @SiO 2 NPs was explained by Istrati et al Based on their report, the SiO 2 layer on the surface of Fe 3 O 4 can result in a steric barrier against core agglomeration, preventing interactions between nanoparticles, which plays a key role in increasing the stability of the Fe 3 O 4 NPs in the solution. In another study, Irani et al employed amino-functionalized graphene oxide nanodispersion in a bubble column absorber and increased CO 2 uptake up to 16.2% with respect to MDEA solution as a base solvent .…”
Section: Introductionmentioning
confidence: 99%